2019
DOI: 10.1021/acs.nanolett.8b04148
|View full text |Cite
|
Sign up to set email alerts
|

Golden Exosomes Selectively Target Brain Pathologies in Neurodegenerative and Neurodevelopmental Disorders

Abstract: Exosomes, nanovesicles that are secreted by different cell types, enable intercellular communication at local or distant sites. Alhough they have been found to cross the blood brain barrier, their migration and homing abilities within the brain remain unstudied. We have recently developed a method for longitudinal and quantitative in vivo neuroimaging of exosomes based on the superior visualization abilities of classical X-ray computed tomography (CT), combined with gold nanoparticles as labeling agents.Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
268
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(297 citation statements)
references
References 65 publications
3
268
0
Order By: Relevance
“…From then on, MEVs have been increasingly considered as substitutes for MSCs in drug delivery. Efforts have been made to improve the efficacy of MEV-based drug delivery for clinical use (Cheng et al, 2018b;Lang et al, 2018;Sharif et al, 2018;Jo et al, 2019;Li et al, 2019a;Perets et al, 2019;Riazifar et al, 2019). For example, a good manufacturing practice (GMP) standard for large-scale clinical MEVs production based on bioreactor has been established (Mendt et al, 2018).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…From then on, MEVs have been increasingly considered as substitutes for MSCs in drug delivery. Efforts have been made to improve the efficacy of MEV-based drug delivery for clinical use (Cheng et al, 2018b;Lang et al, 2018;Sharif et al, 2018;Jo et al, 2019;Li et al, 2019a;Perets et al, 2019;Riazifar et al, 2019). For example, a good manufacturing practice (GMP) standard for large-scale clinical MEVs production based on bioreactor has been established (Mendt et al, 2018).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…They showed that these gold-iron oxide rich EVs achieved excellent T2 contrast MRI and resulted in efficient photothermal effect in 4T1 cells. Recently, Perets et al (2019) developed a method for longitudinal and quantitative in vivo neuroimaging of exosomes based on the superior visualization abilities of classical X-ray computed tomography (CT), combined with gold nanoparticles as labeling agents. Upon administered intranasally, gold nanoparticle-labeled exosomes could be efficiently tracked by CT (Perets et al, 2019).…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers used CT for tracking intranasally (IN) administered gold-labeled exosomes within the brain (Betzer, Perets, et al, 2017;Betzer, Perets, Barnoy, Offen, & Popovtzer, 2018;Perets et al, 2019). A protocol for direct labeling of exosomes with gold nanoparticles (GNP) was developed.…”
Section: Tomographymentioning
confidence: 99%
“…Before this, EV imaging and tracking methods can serve as a guide to direct the development, optimization, and implementation of EV-based therapeutics. To date, considerable effort has been devoted to develop EV tracking methods using fluorescence imaging (14,15), bioluminescence imaging (16), single-photon emission computed tomography (SPECT) (17), positron emission tomography (PET) (18), computed tomography (CT) (19,20), magnetic resonance imaging (MRI) (21,22), and magnetic particle imaging (23). Among them, MRI is an appealing imaging modality that is used widely in the clinic and has excellent soft-tissue contrast without using ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%